The Saudi- Iranian Conflict and its Repercussions on the Middle East - Rebwar Abdulrahim Abdullah; Azad Othman Salih (QALAAI ZANIST JOURNAL, 2021)
The Kingdom of Saudi Arabia was one of the first countries to recognize the new regime in Iran, and expressed its desire to cooperate with it, but soon the regime turned into a hostile regime, and that as an Islamic religious system, it competes with the Saudi regime in religion, opposes it in doctrine, and opposes it in goals. So the merging of what is a political discrepancy and a conflict with what is a sectarian difference or dispute between them and their allies in this struggle. In addition to the kingdom’s feeling of provocation over the issue of "exporting the Iranian revolution" and its fear of targeting its ruling regime and those of the Gulf states in general.